The creep behavior of long fiber reinforced thermoplastics examined by microstructural simulations. (2nd August 2016) - Fliegener, S.; Hohe, J.; Gumbsch, P.
Abstract: Long fiber reinforced thermoplastics (LFT) appear to be promising for the cost efficient manufacture of lightweight structures by injection or compression molding. One major concern persists in their inherent tendency to creep due to continuous sliding within the thermoplastic matrix. To enable the application of LFT components under significant static loads, a profound knowledge of the interactions between the viscoelastic matrix and the nonwoven, discontinuous fiber reinforcement is necessary. In the present work, these interactions are investigated by micromechanical finite element simulations of computer generated LFT structures. The viscoelastic properties of the neat matrix are experimentally characterized and implemented into the microstructural models by an appropriate constitutive law in the form of a four parameter Burgers model. Since a distinct degree of nonlinearity is observed, the applied model is extended to the nonlinear viscoelastic regime and found to be suitable for an accurate reproduction of the experimental data. Micromechanical creep simulations which incorporate the viscoelastic matrix behavior are then validated against creep experiments on LFT specimens of three material variants with a different fiber fraction (PPGF10, PPGF20 and PPGF30), which are loaded under two different orientations at multiple stress levels. The model predictions show a good agreement to the experimental results in particular for the lower and medium stress levels, whereas a slightly increased error can be observed for the highest stress levels. By the application of different variants of the viscoelastic matrix model it is shown that the effects of nonlinearity on the effective creep behavior of the composite are quite considerable. Finally, the evolution of stress and strain within the microstructure during the creep period is visualized by contour plots at different times. The redistribution of stress from the viscoelastic matrix to the elastic fibers can clearly be observed.